Examining the relation between education, recidivism & crime prevention - Georgios Chloupis; Despoina Kontompasi (Discover Global Society)
Abstract This article examines the relation between education in prisons and the reduction of recidivism, assessing the potential benefits of prison education and vocational programs at an international scale. Four main pillars of effects of the educational approach as a leading characteristic of criminal justice policy are discussed, concerning the reducing of reoffending and crime related behavior, the reducing of the social cost of crime, the development of positive social skills and restructure of self-image and self-identity and the facilitation of post-prisoners reintegration. The methodology used pertains to a mixed-method research analysis, involving the review of qualitative and quantitative data (i.e. existing literature, statistics, case studies, expert opinions). Comments and qualitative links are formulated to identify the true relation between education and recidivism rates as well as gray areas related to emerging trends in existing reviews. The findings are discussed with regard to the feasibility of adopting and implementing an education-oriented criminal justice policy, based on a diagnostic analysis point.